Administrasi, Analisis Butir, dan Kaidah Penulisan Tes - ., Khaerudin (Madaniyah, 2017)
Test is a measuring tool used to detect the material which has not been well understood by the students. As a barometer, of course, like the "detector" should be able to detect which parts are healthy, and the portions are ill and require intensive treatment.Â  For the test maker, the analysis is the empirical validity. The item test standard is the item which is equipped with its administration (SK, KD, indicators and number of items), qualitative analysis (the study of items test) up to quantitative analysis. In performing the analysis items, the item writer/maker could analyze qualitatively, in terms of content and form, and quantitative in terms of its statistical characteristics or procedures increases in judgment and procedure improvement empirically. Purpose of study is to assess and examine each item on the matter in order to obtain the grade/the good items before used. In addition, the purpose of items analysis as well to increase the test through revision or dispose of a test that is not effective, and to investigate the diagnostic information on students whether they have / have not understand the material being taught. The good item test is a test that can provide information as precisely as possible in accordance with the purpose of which learners/student can determine which one has or has not mastered/understood the material taught by teacher.